Microsatellite instability as an expert biomarker in cancer diseases - Bondar, O. (Journal of Education, Health and Sport, 2024)
The diagnostic and predictive activities of the oncology service are based on a wide range of immunohistochemical and genetic studies with a different spectrum of applications and different levels of efficacy. An analysis of the results obtained are given which outlined the issues of oncopathology of various localization genetic diagnostics efficacy by determining the level of damaged loci with a typical structure – microsatellites onside the genome of tumour cells. The diagnostic importance of microsatellite instability degree was clarified to determine the oncological diseases manifestation prognosis and the risks of malignancy, including metastasis. The author noted the necessity of patient's RER+ status correct interpretation. Based on the results analysis the conclusions were made regarding the value of microsatellite instability genetic marker determination as an additional criterion of oncopathology which allows predicting certain malignant neoplasms clinical manifestation and determining the risks of metastasis of tumours with varying degrees of microsatellite instability.